Emerging markets in an upside down world : challenging perceptions in asset allocation and investment - Booth, Jerome P. (Jerome Paul) (Wiley, 2014)
The world is upside down. The emerging market countries are more important than many investors realise. They have been catching up with the West over the past few decades. Greater market freedom has spread since the end of the Cold War, and with it institutional changes which have further assisted emerging economies in becoming more productive, flexible, and resilient. The Western financial crisis from 2008 has quickened the pace of the relative rise of emerging markets - their relative economic power, and with it political power, but also their financial power as savers, investors and.